PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) TERHADAP HASIL BELAJAR RENANG GAYA BEBAS (CRAWL) (STUDI PADA SISWA KELAS X JURUSAN TEKNIKA KAPAL PENANGKAP IKAN SMK NEGERI 4 PROBOLINGGO) - BAIHAQI M, FIRLY (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract In the process of teaching and learning in schools, Physical Education, Sport, and Health (Penjasorkes) as other subjects have a curriculum geared to achieve the goals set. The main emphasis of Penjasorkes learning is how to make students happy and excited in doing activities of motion. In this case the teacher plays an important role as a key element in improving children's learning in the nation's schools is the quality of teachers. Success of the learning process is determined by many factors including the factor of teachers in implementing the teaching and learning process, because teachers can directly affect, creating and improving intelligence and skills of students. Cooperative learning has been developed and researched, there are various models of cooperative learning among other achievemen Student Team Division (STAD), Team Games Tournament (TGT), Team-assited Individualization (TAI), Cooperative Integrated Reading and Composition (CIRC), Learning Together and jigsaw II. The purpose of this research is to determine whether or not and how much influence cooperative learning model Team Games Tournament (TGT) on learning outcomes freestyle (crawl) in class X shipping department Vocational High School 4 Probolinggo. Objectives of this study are X class shipping department Vocational School District 4 probolinggo the total sample of 36 students. Methods in the analysis of this data using methods of experimental research with quantitative descriptive approach. Conclusion of the study are: consultation on valuable tcount  (7,244) > ttable (2,042) any difference who significant model kooperatif learning tipe team games tournament (TGT) on learning discution free style swimming (crawl) in class X shipping department Vocational High School 4 Probolinggo with upgrading 9,7%. Keywords: Learning, Study Team Games Tournament, Swimming Freestyle.